Digital literacy among older adults in Singapore - TADAI, Mindy Eiko (Institutional Knowledge at Singapore Management University, 2023)
Singapore stands as the fourth most digitally competitive country, after Denmark, USA, and Sweden, in the latest edition of the IMD World Digital Competitiveness Ranking (IMD World Competitiveness Center, 2022). This global ranking measures the capacities of 63 nations to adopt and explore digitally transformative practices across government, industry, and wider society. Among households in Singapore, an astounding 99% have Internet access and 92% have computer access (Infocomm Media Development Authority, 2023). Even within the eldest surveyed cohort, proportions of smartphone usage have risen from 28% in 2017 to 48% in 2021 among resident Singaporeans aged 75 and above, and the proportion of Singaporeans using the internet has risen from 15% in 2017 to 52% in 2021 (Infocomm Media Development Authority, 2023). While older adults have made significant digital gains in recent years, they remain outpaced by younger generations in terms of digital ownership, usage, and literacy. National and global statistics may be misleading, however, as rising proportions of digital ownership and Internet accessibility may not necessarily correspond with levels of digital literacy. In other words, there is more to the digital divide than meets the eye. The reality for some older adults may be one of shallow participation in a pool of rich social, cognitive, and health-related resources in digital spaces. Thus, adopting a digital literacy lens may be useful for measuring how far Singapore has come in terms of digital transformation within society and for identifying what more needs to happen to ensure that older adults are able to reach a certain level of digital proficiency that affords them meaningful opportunities to stay socially connected and cognitively engaged.